Potential impacts of the mean sea level rise on the hydrodynamics of the Douro river estuary - Mendes, Renato (2018)
Numerous studies based on tide gauge records demonstrated the sea level rise on the Portuguese coast during the last century. Different climatic models predict a mean sea level rise for this coast ranging between 0.28 m and 0.42 m, for the period 2091–2100 relative to 1980–1999. Thus, the potential evaluation of the sea level rise impact on the Portuguese coast becomes critical, especially in sensitive areas as estuaries. The main aim of this work is to evaluate hydrodynamic changes in the Douro estuary induced by the sea level rise. A baroclinic finite volume numerical model was implemented to the Douro estuary in a 2D mode. The model calibration was performed comparing predicted and observed sea surface elevation time series for several stations. The tidal input at the ocean open boundary forces the 2D hydrodynamic model considering actual and future mean sea levels. At the landward boundary the model is forced with the freshwater discharge. The research explores changes in current velocity and amplitude and phase differences of the main diurnal and semi-diurnal tidal constituents along the estuary. The results suggest local significant changes in the Douro hydrodynamics in response to the sea level rise. Nevertheless, the differences don't affect the general estuary’s circulation. Concerning the main tidal constituents, the amplitude increases and the phase decreases, revealing that the tide tends to propagate faster upstream and with higher tidal ranges. Owing to the increasing of the amplitude and the water level, the current velocity values tend to decrease in the estuary, mainly near the low-lying areas.